Biosecurity dilemmas : dreaded diseases, ethical responses, and the health of nations - Enemark, Christian (Georgetown University Press, 2017)
Biosecurity Dilemmas examines conflicting values and interests in the practice of "biosecurity," the safeguarding of populations against infectious diseases through security policies. Biosecurity encompasses both the natural occurrence of deadly disease outbreaks and the deliberate or accidental release of biological weapons. Enemark focuses on six dreaded diseases that are given high-priority by governments and international organizations for research, regulation, surveillance, and rapid response: pandemic influenza, drug-resistant tuberculosis, smallpox, Ebola virus, bubonic plague, and anthrax. The book is organized around four ethical dilemmas that arise when fear causes these diseases to be framed in terms of national or international security: protect or proliferate, secure or stifle, remedy or overkill, and attention or neglect. For instance, will prioritizing research into defending against a rare event such as a bioterrorist attack divert funds away from research into commonly occurring diseases? Or will securitizing a particular disease actually stifle research progress due to security classification measures? Enemark provides a comprehensive analysis of the ethics of securitizing disease and explores ideas and policy recommendations about biological arms control, global health security, and public health ethics.